1997
DOI: 10.1093/toxsci/38.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Methoxyacetic Acid in Cultured Human Luteal Cells

Abstract: Ethylene glycol monomethyl ether (EGME) and its proximate metabolite, 2-methoxyacetic acid (MAA), increase ovarian luteal cell progesterone production in the female rat in vivo and in cultured rat luteal cells in vitro, respectively. In order to better assess the potential hazard of EGME and MAA to women, these studies were conducted to determine whether the same concentrations of MAA increase progesterone in human luteinized granulosa cells as in rat luteal cells. Human cells were collected from healthy anony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Our initial studies led us to ethylene glycol monomethyl ether (EGME), a pervasive industrial solvent found in varnishes, paints, dyes, and fuel additives. Exposure to this compound and its primary metabolite MAA induce severe reproductive toxicity in both humans and rodents (11,12). Based on reports that toxic doses of EGME give rise to 5 mM MAA plasma levels in rodents and that similar concentrations of MAA are observed in the urine of humans after occupational EGME exposure (13,14), we treated cells with 5 mM MAA to achieve comparable MAA levels for our studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial studies led us to ethylene glycol monomethyl ether (EGME), a pervasive industrial solvent found in varnishes, paints, dyes, and fuel additives. Exposure to this compound and its primary metabolite MAA induce severe reproductive toxicity in both humans and rodents (11,12). Based on reports that toxic doses of EGME give rise to 5 mM MAA plasma levels in rodents and that similar concentrations of MAA are observed in the urine of humans after occupational EGME exposure (13,14), we treated cells with 5 mM MAA to achieve comparable MAA levels for our studies.…”
Section: Resultsmentioning
confidence: 99%
“…8 9 This metabolite altered the ovarian luteal function, and increased ovarian luteal cell progesterone production in female rats 10 and in cultured human cells. 11 Previous epidemiological studies suggested that long cycles may indicate delayed ovulation, 27 and short cycles may reflect a short follicular phase 28 or anovulation. 29 Exposure to EGEs was associated with prolonged time to pregnancy in female fab workers.…”
Section: Discussionmentioning
confidence: 99%
“…7 Animal studies and human culture cells have suggested that the major metabolite of ethylene glycol monomethyl ether, 2-methoxyacetic acid, is most significantly associated with the increase of these risks. [8][9][10][11] Few studies 12 13 have discussed the relation between occupational exposure to contaminants and a change in menstrual cycles. A prospective semiconductor industry study 12 found that the mean and standard deviation of the cycle length were significantly greater among female workers engaged in thin film and ion implantation jobs than among non-fabrication (non-fab) workers.…”
mentioning
confidence: 99%
“…In female rats, EGME induces PRL secretion (Taketa et al, ). EGME and its active metabolite, 2‐methoxy acetic acid, are also known to induce the hypersecretion of P4 from luteal cells (Almekinder et al, ; Davis et al, ).…”
Section: Introductionmentioning
confidence: 99%